A study case of passive bilingualism of individuals in Scottish Gaelic Community - Salmon Pandarangga (Jurnal Inspirasi Pendidikan, 2015)
There are so many different definition and perspective of bilingualism that particularly link to active and passive bilingualism as so many scholars and experts still debated and even contradicted themselves about bilingualism and its definition. It is thus this paper aims to define the definition of bilingualism based on elaboration of some scholars such as Beardsmore, Collin, Skutnabb-Kangas and others. The finding indicates that the ability to use two languages either actively or passively highly related to the level of proficiency. The author also proposes that those who use the other language for limited vocabulary or who understand but not produce the language still considered as bilinguals.        Keywords : bilingualism, bilinguals, proficiency, competence.